DETERMINING THE EFFECTIVENESS OF USING CHATGPT-4 IN ORGANISING EXCURSIONS - ISSAKOV, Yerlan; OMAROV, Kairat; SAVANCHIYEVA, Armanay; KADYRBEKOVA, Dinara; ALDASHEVA, Ardak; BEKEN, Akbota; TOKENOVA, Zhanerke; DÁVID, Lóránt Dénes (Geo Journal of Tourism and Geosites, 2024)
As artificial intelligence (AI) technology becomes more deeply embedded in people's daily lives and work, the importance of ChatGPT (Generative Pretrained Transformer) is growing and its application in the tourism sector is expanding. ChatGPT can be useful in organising new excursions because of its capabilities such as data analysis, interpretation, scenario creation and model evaluation. Therefore, the purpose of this study was to determine the effectiveness of using ChatGPT-4 in organising new excursions. The study was conducted at the Abai Kazakh National Pedagogical University and 82 students participated in the study. The study consisted of two stages, at the first stage students answered a questionnaire on the discipline of "Literary excursion", which was studied for 15 weeks, and at the second stage was conducted a study based on comparative analysis, with the assignment of 6 specially prepared questions to determine the effectiveness of using ChatGPT-4. As a result of the study, the need to study the excursion subject for students of educational programmes "Kazakh language and literature" was 72%. ChatGPT-4 became an indispensable tool in drawing up excursion itineraries for students, making their technological map and selecting an excursion object. In addition, with the help of ChatGPT-4 students built routes of new excursions and correctly identified tourist objects and traffic routes, type. Also very qualitatively wrote the text of the excursion in lit erary language and brought it to the level of an interesting script. Thus, using ChatGPT-4 when organising new excursions will help you to get information, save time, make specific decisions and improve quality. The results of this study may be useful in th e future to explore ChatGPT-4 in the potential integration of other technologies such as augmented reality or virtual reality.